Simulation Political Branding #Ganjarpresiden2024 Base on Media Sosial Analysis - Ivan Taufiq; Yudi Daherman (Calathu: Jurnal Ilmu Komunikasi, 2024)
Talking about 2024 is certainly talking about the political year in Indonesia. Year of 2024 is the year when legislative candidates and of course presidential and vice-presidential candidates starts contesting. Currently, one of the presidential candidates from the party that won the 2014 and 2019 elections is Ganjar Pranowo. As one of the presidential candidates in 2024, Ganjar Pranowo really needs to present himself as a person who deserves to be the president of Indonesia in 2024, so it is important for Ganjar Pranowo to utilize his social media and then through the concept of hyperreality give an effect to a wide audience through social media. This research was conducted to find out how Ganjar Pranowo's political branding simulation in preparation for the 2024 Presidential Election is based on big data analysis on Tiktok social media through content related to Ganjar's candidacy as a Presidential candidate in 2024. The focus of the research is the arrangement and meaning of #GanjarPresiden2024 signs and messages on mainstream social media received by digital society and then forming a simulation of Ganjar Pranowo's political branding which is the result of the digital communication process towards Ganjar's political representation as a 2024 presidential candidate. The research method uses Jean Baudrillard's theory with a simulation approach.